2023
DOI: 10.1002/mds.29580
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐Based Dietary Patterns and Parkinson's Disease: A Prospective Analysis of the UK Biobank

Anna Tresserra‐Rimbau,
Alysha S. Thompson,
Nicola Bondonno
et al.

Abstract: BackgroundPlant‐based diets have been associated with a lower risk of several chronic diseases, but the relationship with PD is unknown.ObjectivesWe examined the association of three different plant‐based diets with PD incidence in the UK Biobank cohort.MethodsWe conducted a prospective study among 126,283 participants from the UK Biobank cohort. Three plant‐based diet indices (overall plant‐based diet index, PDI; healthful plant‐based diet index, hPDI; and unhealthful plant‐based diet index, uPDI) were derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Limited prior epidemiological studies have suggested lower rates of PD in societies mostly following vegetarian and vegan diets [29][30][31]. A recent UK biobank analysis found an association between a healthful plant-based diet and reduced PD risk (HR = 0.78 (95% CI: 0.61-0.99)), whereas an unhealthy plant-based diet was associated with a higher risk to develop PD (HR = 1.38 (95% CI: 1.08-1.74)) [32]. One recent trial of a 14-day ovo-lacto vegetarian diet in 16 patients with PD demonstrated significant improvements in UPDRS Part III scores [33].…”
Section: Vegetarian and Vegan Dietsmentioning
confidence: 99%
“…Limited prior epidemiological studies have suggested lower rates of PD in societies mostly following vegetarian and vegan diets [29][30][31]. A recent UK biobank analysis found an association between a healthful plant-based diet and reduced PD risk (HR = 0.78 (95% CI: 0.61-0.99)), whereas an unhealthy plant-based diet was associated with a higher risk to develop PD (HR = 1.38 (95% CI: 1.08-1.74)) [32]. One recent trial of a 14-day ovo-lacto vegetarian diet in 16 patients with PD demonstrated significant improvements in UPDRS Part III scores [33].…”
Section: Vegetarian and Vegan Dietsmentioning
confidence: 99%
“…In a notable publication, the “Plant-Based Dietary Patterns and Parkinson’s Disease: A Prospective Analysis of the UK Biobank” large-scale prospective study attempted to analyze data from the UK Biobank to assess the impact of plant-based diets on the incidence of Parkinson’s disease [5]. The UK Biobank is a large-scale biomedical database and research initiative established to improve the prevention, diagnosis, and treatment of a wide range of diseases and conditions.…”
Section: Knowledge Transfer Of Liana Poulia (Athens)mentioning
confidence: 99%